The effect of peripheral dopamine on fracture healing: an experimental study in a rat model - Mücahid Osman Yücel; Raşit Emin Dalaslan; Sönmez Sağlam; Mehmet Arıcan; Zekeriya Okan Karaduman; Banu Turhan; Fatih Demir (Journal of Orthopaedic Surgery and Research)
Abstract Background Dopamine is a versatile biomolecule that functions as a neurotransmitter, hormone, and immune modulator in the body. Although some anabolic effects of dopamine on bone tissue have been described in the literature, its influence on the complex processes involved in fracture healing remains unclear. This study aimed to evaluate the effects of dopamine on bone healing at the peripheral level. Methods Thirty-six male Wistar albino rats were randomly assigned to two groups: a control group with no treatment and a dopamine group that received 12 mg/kg levodopa twice daily via oral gavage following surgery. A standardized femoral fracture was induced under anesthesia in all the rats, which were then fixed with an intramedullary Kirschner wire. Each group consisted of 18 rats, and six rats from each group were randomly sacrificed on postoperative days 15, 30, and 45. The harvested femurs were first evaluated radiologically, followed by biomechanical analysis via a three-point bending test, and finally subjected to histopathological examination. Results No significant differences were observed between the groups on days 15 and 30. However, on day 45, histopathological scores were significantly lower in the dopamine group (p = 0.015), and biomechanical strength was also lower (p = 0.004). Radiological scores were not significantly different between the groups at any time point. Conclusion Despite the known anabolic effects of dopamine on bone cells, it may adversely affect fracture healing. The negative impact of dopamine on bone union could be attributed to the multifactorial and complex nature of fracture healing, the dynamics of inflammatory processes, and the cumulative effects of various dopamine receptor subtypes.